Supervisi Akademis oleh Kepala Sekolah terhadap Guru Pendidikan Agama Islam di Sekolah Dasar Negeri 009 Penajam Kab. Penajam Paser Utara - Aji Luqman Panji; Bahrani Bahrani; Sudadi Sudadi (Departement of Mathematics Education, 2023)
One of the functions of this research is to explore the academic supervision conducted by the school principal and its subsequent impact on the changes in the performance of Islamic religious education teachers at State Elementary School 009 Penajam, along with the influencing factors. This study employs a field study method with a qualitative approach. The research results indicate that the academic supervision carried out by the school principal includes aspects of learning planning by providing guidance in formulating learning objectives, overseeing the implementation of learning by providing an example in initiating and presenting materials, and guiding the evaluation of learning by assisting in the preparation of assessment tools. Several factors influencing academic supervision activities include support from teachers who are the objects of supervision, where a teacher's cooperation and openness in the implementation of supervision by the supervisor are supportive factors. Conversely, inhibiting factors in the implementation of principal supervision include the limited time allocation for Islamic religious education in elementary school.